Developing Marine and Fisheries Industry in Pangandaran Following a Bioecoregion-Based Technopark Framework - Atikah Nurhayati; Agus Heri Purnomo (STI Policy and Management Journal, 2017)
From the bioecoregional point of view, the Pangandaran Regency is a land-water-mass with a strong ecological connectivity, and which also is chareacterized by the dominance of marine and fisheries resource potentials. In this region, a number of development variables exists and are available for transforming these natural resources into an advanced industry, which can sustain the region’s economy. Recognizing such a premise, this research aims at analyzing those variables in more detail, as associated with efforts to accellerate the establishment of a strong economy which is supported by a marine and fisheries industry in Pangandaran. The technopark concept is taken as the main reference for the industry to be developed while the gap analysis is taken as the research’s primary methodological approach. Primary and secondary data collected through literature study, discussion, consultation, field visits, and Focus Group Discussion (FGD) are used to carry out the gap analysis, which is then followed up by the SWOT analysis. Based on the research, it can be concluded that the existing bioecoregional setting as well as the available development variables are conducive to facilitate development of a marine and fisheries technopark as long as a number of improvement are carried out. A proposal to operationalize such improvements as suggested by the result of this research is demonstrated in a roadmap as presented in the final section of this paper.